2020
DOI: 10.1016/j.antiviral.2020.104786
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir, lopinavir, emetine, and homoharringtonine inhibit SARS-CoV-2 replication in vitro

Abstract: An escalating pandemic by the novel SARS-CoV-2 virus is impacting global health and effective therapeutic options are urgently needed. We evaluated the in vitro antiviral effect of compounds that were previously reported to inhibit coronavirus replication and compounds that are currently under evaluation in clinical trials for SARS-CoV-2 patients. We report the antiviral effect of remdesivir, lopinavir, homorringtonine, and emetine against SARS-CoV-2 virus in Vero E6 cells with the estimated 50% effective conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
900
8
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 856 publications
(984 citation statements)
references
References 33 publications
30
900
8
27
Order By: Relevance
“…It is also used to induce vomiting. In addition, it possessed antiviral effects against ZIKV, EBOV, RABV, CMV, HCoV-OC43, HSV-2, EV1, HMPV, RVF, FLUAV, HIV-1 and SARS-CoV-2 (Andersen et al, 2019;Chaves Valadao et al, 2015;Choy et al, 2020;MacGibeny et al, 2018;Mukhopadhyay et al, 2016;Shen et al, 2019;Yang et al, 2018) (https://doi.org/10.1101/2020.03.25.008482). Emetine was proposed to inhibit viral polymerases, though it could have some other targets (Khandelwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used to induce vomiting. In addition, it possessed antiviral effects against ZIKV, EBOV, RABV, CMV, HCoV-OC43, HSV-2, EV1, HMPV, RVF, FLUAV, HIV-1 and SARS-CoV-2 (Andersen et al, 2019;Chaves Valadao et al, 2015;Choy et al, 2020;MacGibeny et al, 2018;Mukhopadhyay et al, 2016;Shen et al, 2019;Yang et al, 2018) (https://doi.org/10.1101/2020.03.25.008482). Emetine was proposed to inhibit viral polymerases, though it could have some other targets (Khandelwal et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Homoharringtonine is an anticancer drug which is indicated for treatment of chronic myeloid leukaemia. It also possesses antiviral activities against HBV, MERS-CoV, HSV-1, EV1, VZV and SARS-CoV-2 (Andersen et al, 2019;Cao et al, 2015;Choy et al, 2020;Dong et al, 2018;Kim and Song, 2019;Romero et al, 2007). Homoharringtonine binds to the 80S ribosome and inhibits viral protein synthesis by interfering with chain elongation (Dong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 14 key studies that detailed the antiviral activity of 72 compounds [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Table 1.…”
Section: Identified Papers and Methodsmentioning
confidence: 99%
“…2,4,5 In vitro, remdesivir inhibited replication of SARS-CoV-2. 6,7 Moreover, in vitro experiments have shown that mutations conferring resistance to remdesivir do not easily emerge in coronaviruses 8 . Here, we investigated the efficacy of remdesivir treatment in our recently established rhesus macaque model of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%